Penegakan Hukum Terhadap Sungai Taluduyunu Akibat Pencemaran Limbah Pertambangan - Putri Regina Datunsolang; Fenty Puluhulawa; Ahmad Ahmad (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study aims to evaluate the effectiveness of existing law enforcement related to environmental pollution in the Taluduyunu River. The method used in the study is normative and then analyzed in a descriptive qualitative. The results showed that the basis of law enforcement evaluation of the Taluduyunu River due to pollution of mining waste (Case Study Buntulia District, Pohuwato Regency). The results of this study revealed that law enforcement against river pollution due to mining waste is still not effective. Despite clear regulations regarding waste disposal, many mining companies have not fully complied with these regulations. Increased coordination between government agencies, the application of more stringent sanctions, as well as environmental awareness on the part of the industry are needed to thoroughly address this issue. To improve the effectiveness of law enforcement, there is a need for stricter policy reforms, increased capacity of law enforcement institutions, and closer collaboration between government, industry, and civil society in an effort to maintain environmental sustainability and public health affected by mining waste pollution.